مكانة اللغة من الهُوية في كتابات أحمد بن نعمان من خلال كتابيه : التعريب والهُوية الوطنية - دراسة اجتماعية للغة - كوت, شروق; قرفي, أميرة (جامعة الوادي - university of eloued, 2023)
مكانة اللغة من الهُوية في كتابات أحمد بن نعمان من خلال كتابيه : التعريب والهُوية الوطنية - دراسة اجتماعية للغة In our research, we have dealt with an important topic related to identity, as we have touched on the status of language in identity, and we have devoted the hadith to that through the writings of Ahmed bin Noman, especially his books Arabization and National Identity, where we tried in this work to search for the relationship that links language with identity and the role of language In preserving the identity of peoples, we have finally concluded that language and identity are like body and soul, both of which require the presence of one of them the presence of the other, so any fluctuation in the official language or pluralism leads to the loss of national identity.
لسانيات عامة
Keywords: اللغة ، مكانة اللغة من الهوية ، كتابا أحمد بن نعمان ، التعريب والهوية الوطنية; language, the status of language in identity, Ahmed bin Noman's books, Arabization and national identity